Composite positive pole piece, preparation method thereof and lithium ion battery

By setting a solid electrolyte layer on the positive electrode active material layer of the lithium-ion battery, the problem of insufficient safety during use of the lithium-ion battery is solved, and higher safety and lower preparation costs are achieved.

CN119627066APending Publication Date: 2025-03-14XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411665883.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing lithium-ion batteries, especially ternary lithium-ion batteries, may experience safety problems such as thermal runaway, combustion and even explosion during use. The existing solutions cannot comprehensively improve the safety of the battery.

Method used

A solid electrolyte layer is provided on the positive electrode active material layer. Through this structural design, the battery exhibits higher safety in needle puncture, overcharge and short circuit tests.

Benefits of technology

By providing a solid electrolyte layer on the positive electrode active material layer, the safety of the battery is comprehensively improved, and thermal stability can be improved and cost and preparation process complexity can be reduced without affecting electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627066A_ABST
    Figure CN119627066A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a composite positive pole piece, a preparation method of the composite positive pole piece and a lithium ion battery, the composite positive pole piece comprises a positive current collector, a negative current collector, a positive electrode and a negative electrode, and the positive current collector is provided with two opposite surfaces; the positive electrode active material layer is arranged on at least one surface of the positive electrode current collector; and the solid electrolyte layer is arranged on the positive electrode active material layer. According to the lithium ion battery, the solid electrolyte layer is arranged on the positive active material layer, so that the battery can pass needling, overcharge and short-circuit test inspection, and the use safety of the lithium ion battery is comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite positive electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art

[0002] With the development of science and technology, lithium batteries are widely used in various electronic devices, electric vehicles and other fields due to their high energy density, long cycle life and environmental protection. However, the safety performance of lithium batteries has always been the focus of people's attention, especially ternary lithium-ion batteries. Due to their high energy density and chemical activity, they may have safety problems such as thermal runaway, combustion and even explosion during use. Therefore, how to improve the safety performance of lithium batteries, especially the safety performance of ternary lithium-ion batteries, is a technical problem that needs to be solved urgently in the current field of lithium battery manufacturing technology.

[0003] The existing solutions mainly improve the safety of batteries by improving the structural design of batteries and optimizing the material formula of batteries. For example, by adding a heat dissipation device to the battery, the thermal stability of the battery can be improved, thereby improving the safety of the battery. In addition, the safety of the battery can also be improved by designing a flame-retardant electrolyte. However, the above solutions can only improve the safety of the battery in terms of overcharge or short circuit, but cannot improve the safety in terms of needle puncture, and therefore cannot improve the safety of the battery in an all-round way. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a composite positive electrode plate and a preparation method thereof and a lithium-ion battery. The present invention provides a solid electrolyte layer on the positive electrode active material layer, which helps the battery to pass puncture, overcharge and short-circuit test inspections, thereby comprehensively improving the safety of lithium-ion batteries.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a composite positive electrode sheet, the composite positive electrode sheet comprising:

[0007] A positive electrode current collector having two opposite surfaces;

[0008] A positive electrode active material layer, the positive electrode active material layer is disposed on at least one surface of the positive electrode current collector;

[0009] A solid electrolyte layer is provided on the positive electrode active material layer.

[0010] The present invention provides a solid electrolyte layer on the positive electrode active material layer, which helps the battery pass the needle puncture, overcharge and short circuit test inspections, and comprehensively improves the use safety of the lithium ion battery.

[0011] Further, the positive electrode current collector comprises aluminum foil;

[0012] And / or, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate, and lithium manganese oxide;

[0013] and / or, the thickness of the solid electrolyte layer is 5 to 15 microns;

[0014] And / or, the solid electrolyte layer includes a solid electrolyte, and the solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, LLTO, and LLZTO;

[0015] And / or, the solid electrolyte layer further includes a binder, and the binder includes at least one of PVDF (polyvinylidene fluoride) and PEO (polyethylene oxide).

[0016] Furthermore, the mass ratio of the solid electrolyte to the binder is (70-95):(5-30).

[0017] In a second aspect, the present invention provides a method for preparing the composite positive electrode sheet as described in the first aspect, the preparation method comprising:

[0018] S1, mixing a solid electrolyte and a binder to obtain a mixture, then adding the mixture to a solvent and stirring evenly to obtain the solid electrolyte solution;

[0019] S2. Applying the solid electrolyte solution on a positive electrode body and drying it to obtain the composite positive electrode sheet, wherein the positive electrode body includes the positive electrode collector and the positive electrode active material layer arranged on at least one surface of the positive electrode collector.

[0020] Further, the solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, LLTO, and LLZTO, the binder includes at least one of PVDF and PEO, and the solvent includes at least one of NMP and acetonitrile;

[0021] And / or, the mass ratio of the solid electrolyte to the binder is (70-95):(5-30);

[0022] And / or, in step S1, the mass of the solvent in the solid electrolyte solution accounts for 65% to 85% of the mass of the solid electrolyte solution.

[0023] Further, in step S2, during the coating process, the coating speed is 1-10 m / min;

[0024] and / or, in step S2, during the coating process, the coating pressure is 0.1 to 10 MPa;

[0025] And / or, in step S2, the drying temperature is 80-120° C., and the drying time is 5-30 min.

[0026] Furthermore, the preparation method of the positive electrode body includes: preparing the positive electrode active material, conductive agent and binder into a positive electrode slurry, coating the positive electrode slurry on the positive electrode current collector to obtain the positive electrode active material layer, and then rolling and die-cutting to obtain the positive electrode body.

[0027] Furthermore, in the preparation process of the positive electrode body, the conductive agent includes at least one of conductive carbon black, Ketjen black, acetylene black, carbon nanotubes, and graphene, and the binder includes at least one of PVDF, polytetrafluoroethylene, polyacrylonitrile, polyvinyl alcohol, and polyacrylic acid.

[0028] Furthermore, during the preparation of the positive electrode body, the single-sided surface density of the coating is 15-25 mg / cm 2 .

[0029] In a third aspect, the present invention provides a lithium-ion battery, comprising the composite positive electrode sheet described in the first aspect or the composite positive electrode sheet prepared by the preparation method described in the second aspect.

[0030] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:

[0031] (1) The present invention provides a solid electrolyte layer on the positive electrode active material layer, which helps the battery pass the needle puncture, overcharge and short circuit tests, thereby comprehensively improving the safety of lithium-ion batteries.

[0032] (2) Improving thermal stability: The present invention can effectively improve the thermal stability of the positive electrode sheet by coating a solid electrolyte layer on the surface of the positive electrode sheet, thereby improving the safety of the lithium-ion battery. The present invention can solve the overall safety problem while balancing the electrical performance of the battery.

[0033] (3) Reducing the impact on energy density and electrical performance: The present invention can reduce the impact on energy density and electrical performance while ensuring safety performance by adjusting the mass ratio of different solid electrolytes and binders and controlling the thickness of the modified layer through coating parameters. This is often impossible to do in the prior art because the existing solutions often require large-scale modification of the battery structure, which not only increases the manufacturing cost of the battery, but may also affect the energy density and electrical performance of the battery.

[0034] (4) Reduce costs and complexity of the preparation process: Although the existing technical solutions can improve the safety of the battery, their preparation process is complex and the cost is high. The present invention can reduce the preparation cost and process complexity by optimizing the mass ratio of materials and coating parameters, while also avoiding possible impacts on the electrical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 This is a schematic diagram of the structure of the composite positive electrode plate provided by the present invention.

[0037] Icon: 1-positive electrode current collector, 2-positive electrode active material layer, 3-solid electrolyte layer. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0039] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0040] Figure 1 A schematic diagram of the structure of the composite positive electrode sheet provided by the present invention, such as Figure 1 As shown, in a first aspect, the present invention provides a composite positive electrode sheet, the composite positive electrode sheet comprising:

[0041] A positive electrode current collector 1, wherein the positive electrode current collector 1 has two opposite surfaces;

[0042] A positive electrode active material layer 2, wherein the positive electrode active material layer 2 is disposed on at least one surface of the positive electrode current collector 1;

[0043] The solid electrolyte layer 3 is disposed on the positive electrode active material layer 2 .

[0044] The present invention provides a solid electrolyte layer on the positive electrode active material layer, which helps the battery pass the needle puncture, overcharge and short circuit test inspections, and comprehensively improves the use safety of the lithium ion battery.

[0045] In the above composite positive electrode sheet, as an optional implementation, the positive electrode current collector 1 includes aluminum foil.

[0046] In the above-mentioned composite positive electrode sheet, as an optional embodiment, the positive electrode active material layer 2 includes a positive electrode active material, and the positive electrode active material includes one of lithium nickel cobalt manganese oxide (NCM), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), and lithium manganese oxide (LiMn2O4).

[0047] In the above-mentioned composite positive electrode sheet, as an optional embodiment, the thickness (single-side thickness) of the solid electrolyte layer 3 is 5 to 15 microns, for example, it can be 5 microns, 10 microns or 15 microns. If the solid electrolyte layer is too thick: the resistance of the solid electrolyte layer will increase, resulting in an increase in the internal resistance of the battery, thereby affecting the output power and energy density of the battery; the increase in the thickness of the solid electrolyte layer may cause the conductivity of ions in the electrolyte layer to decrease, thereby affecting the charge and discharge performance of the battery. If the solid electrolyte layer is too thin: the thickness of the solid electrolyte layer is reduced, which may cause its mechanical strength to decrease, and it is easy to be damaged during the use of the battery, thereby affecting the safety of the battery; the solid electrolyte layer is too thin, which will cause problems at the interface between the solid electrolyte layer and the positive electrode material, resulting in an increase in the interface resistance, thereby affecting the performance and safety of the battery.

[0048] In the above-mentioned composite positive electrode sheet, as an optional embodiment, the solid electrolyte layer 3 includes a solid electrolyte, and the solid electrolyte includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), LLTO (lithium lanthanum titanium oxide), and LLZTO (lithium lanthanum zirconium titanium oxide).

[0049] In the above composite positive electrode sheet, as an optional implementation, the solid electrolyte layer 3 further includes a binder, and the binder includes at least one of PVDF (polyvinylidene fluoride) and PEO (polyethylene oxide).

[0050] In the above composite positive electrode sheet, as an optional embodiment, the mass ratio of the solid electrolyte to the binder is (70-95):(5-30), for example, it can be 70:30, 80:20, 85:15, 90:10 or 95:5.

[0051] In the above composite positive electrode sheet, as an optional embodiment, the mass of the solid electrolyte accounts for 70% to 95% of the sum of the mass of the solid electrolyte and the binder, for example, it can be 70%, 80%, 85%, 90% or 95%.

[0052] In a second aspect, the present invention provides a method for preparing the composite positive electrode sheet as described in the first aspect, the preparation method comprising:

[0053] S1, mixing a solid electrolyte and a binder to obtain a mixture, then adding the mixture to a solvent and stirring evenly to obtain the solid electrolyte solution;

[0054] S2. Apply the solid electrolyte solution on the positive electrode body and dry it to obtain the composite positive electrode sheet, wherein the positive electrode body includes the positive electrode collector 1 and the positive electrode active material layer 2 arranged on at least one surface of the positive electrode collector 1.

[0055] Here, the positive electrode body can be any common lithium battery positive electrode plate, such as nickel cobalt manganese oxide (NCM) positive electrode plate.

[0056] In the preparation method of the above-mentioned composite positive electrode plate, as an optional embodiment, the solid electrolyte includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), LLTO (lithium lanthanum titanium oxide), and LLZTO (lithium lanthanum zirconium titanium oxide), the binder includes at least one of PVDF (polyvinylidene fluoride) and PEO (polyethylene oxide), and the solvent includes at least one of NMP (N-methylpyrrolidone) and acetonitrile.

[0057] In the method for preparing the composite positive electrode sheet, as an optional implementation, the mass ratio of the solid electrolyte to the binder is (70-95): (5-30).

[0058] In the above-mentioned method for preparing the composite positive electrode sheet, as an optional implementation, the mass of the solid electrolyte accounts for 70% to 95% of the sum of the mass of the solid electrolyte and the binder.

[0059] In the above-mentioned method for preparing the composite positive electrode sheet, as an optional implementation, in step S1, the mass of the solvent in the solid electrolyte solution accounts for 65% to 85% of the mass of the solid electrolyte solution, for example, it can be 65%, 70%, 75%, 80% or 85%.

[0060] In the above-mentioned method for preparing the composite positive electrode sheet, as an optional embodiment, in step S2, during the coating process, the coating speed is 1-10m / min, for example, 1m / min, 3m / min, 5m / min, 7m / min or 10m / min. If the coating speed is too fast: the residence time of the coating liquid on the electrode sheet becomes shorter, which may cause the coating to be uneven and uneven in thickness; rapid coating may increase the porosity of the coating, affecting the ion conductivity of the battery; rapid coating may cause defects such as cracks and holes to appear on the surface of the coating, affecting the performance of the battery. If the coating speed is too slow: a long coating process may increase the viscosity of the coating liquid, affecting the uniformity and fluidity of the coating; slow coating may cause the surface of the coating to dry prematurely, forming a hard shell, hindering the volatilization of the internal solvent and the further curing of the coating; a long coating process may cause the coating uniformity to deteriorate, and defects such as stripes and spots may appear.

[0061] In the preparation method of the composite positive electrode sheet, as an optional embodiment, in step S2, during the coating process, the coating pressure is 0.1 to 10 MPa, for example, 0.1 MPa, 1 MPa, 3 MPa, 5 MPa, 7 MPa or 10 MPa. Effects of excessive pressure: Decreased coating uniformity: Excessive pressure may cause uneven coating on the surface of the electrode sheet, resulting in uneven thickness, which will affect the battery's charge and discharge performance and internal resistance; Pole sheet deformation: Excessive pressure may cause deformation of the electrode sheet, affecting the mechanical strength and dimensional stability of the electrode sheet, which may cause problems during battery assembly, such as electrode sheet breakage or poor contact with the battery housing; Binder damage: Excessive pressure may damage the binder and affect the bonding properties of the binder, which will cause a decrease in the bonding force between the coating and the electrode sheet substrate and increase the risk of coating peeling. Impact of too little pressure: Too little pressure may result in insufficient bonding between the coating and the electrode substrate, increasing the risk of coating peeling, which will affect the battery's cycle stability and safety performance; Uneven coating thickness: Too little pressure may result in uneven coating thickness, with thin coating or uncoated areas, which will affect the battery's charge and discharge performance and internal resistance; Pole surface damage: Too little pressure may not be able to effectively compact the electrode surface, resulting in increased surface roughness of the electrode, which will affect the battery's charge and discharge performance and internal resistance.

[0062] In the preparation method of the above-mentioned composite positive electrode sheet, as an optional embodiment, in step S2, the drying temperature is 80-120°C, for example, it can be 80°C, 90°C, 100°C, 110°C or 120°C, and the drying time is 5-30min, for example, it can be 5min, 10min, 15min, 20min, 25min or 30min.

[0063] In the preparation method of the above-mentioned composite positive electrode sheet, as an optional embodiment, the preparation method of the positive electrode body includes: preparing the positive electrode active material, conductive agent and binder into a positive electrode slurry and coating it on the positive electrode collector 1 to obtain the positive electrode active material layer 2, and then rolling and die-cutting to obtain the positive electrode body.

[0064] In the preparation method of the above-mentioned composite positive electrode plate, as an optional embodiment, during the preparation of the positive electrode body, the conductive agent includes at least one of conductive carbon black (SP), Ketjen black, acetylene black, carbon nanotubes, and graphene, and the binder includes at least one of PVDF, polytetrafluoroethylene, polyacrylonitrile, polyvinyl alcohol, and polyacrylic acid.

[0065] In the above-mentioned method for preparing the composite positive electrode sheet, as an optional embodiment, during the preparation of the positive electrode body, the single-sided surface density of the coating is 15-25 mg / cm 2 , for example, 15 mg / cm 2 、17mg / cm 2 、19mg / cm 2 , 21mg / cm 2 , 23mg / cm 2 or 25 mg / cm 2 .

[0066] In a third aspect, the present invention provides a lithium-ion battery, comprising the composite positive electrode sheet described in the first aspect or the composite positive electrode sheet prepared by the preparation method described in the second aspect.

[0067] In the above lithium-ion battery, as an optional implementation, the lithium-ion battery further includes a negative electrode plate, a separator and an electrolyte.

[0068] The lithium ion battery is prepared by using a conventional lithium ion battery manufacturing process.

[0069] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0070] Example 1

[0071] The present embodiment provides a composite positive electrode plate, which includes: an aluminum foil having two opposite surfaces; a nickel cobalt lithium manganese oxide layer, which is arranged on two opposite surfaces of the aluminum foil; and a LATP layer, which is arranged on the nickel cobalt lithium manganese oxide layer. That is, the composite positive electrode plate is composed of: LATP layer + nickel cobalt lithium manganese oxide layer + aluminum foil + nickel cobalt lithium manganese oxide layer + LATP layer, wherein the single-side thickness of the LATP layer is 10 microns, and the thickness of the aluminum foil is 12 microns.

[0072] The method for preparing the composite positive electrode sheet comprises the following steps:

[0073] S0. Prepare the positive electrode body: prepare positive electrode slurry with NCM, SP and PVDF in a mass ratio of 96:2:2, apply the positive electrode slurry on aluminum foil, roll and die-cut to obtain a positive electrode body with a length and width of 90×59 mm, wherein the single-sided surface density of the positive electrode slurry coating is 19.8 mg / cm 2 , compacted density is 3.5g / cm 3 , where NCM refers to nickel cobalt manganese oxide lithium ternary cathode material, SP refers to conductive carbon black, and PVDF refers to polyvinylidene fluoride;

[0074] S1. Prepare solid electrolyte solution: mix solid electrolyte and binder in a mass ratio of 9:1, wherein the solid electrolyte is solid electrolyte LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), PVDF is selected as the binder, and then the mixture is added to the NMP solvent and stirred evenly to form a solid electrolyte solution, wherein the mass of the NMP solvent accounts for 80% of the mass of the solid electrolyte solution;

[0075] S2. The prepared solid electrolyte solution is evenly coated on the surface of the positive electrode body at a coating speed of 5 m / min and a coating pressure of 0.5 MPa. After coating, the positive electrode body is dried at 80° C. for 30 min to form a solid electrolyte layer to obtain a composite positive electrode sheet.

[0076] The composite positive electrode sheet prepared in this embodiment is assembled into a lithium-ion battery according to a conventional lithium battery manufacturing process, and a lithium-ion battery with high safety performance can be obtained.

[0077] Example 2

[0078] The present embodiment provides a composite positive electrode plate, which includes: an aluminum foil having two opposite surfaces; a nickel cobalt lithium manganese oxide layer, which is arranged on two opposite surfaces of the aluminum foil; and a LATP layer, which is arranged on the nickel cobalt lithium manganese oxide layer. That is, the composite positive electrode plate is composed of: LATP layer + nickel cobalt lithium manganese oxide layer + aluminum foil + nickel cobalt lithium manganese oxide layer + LATP layer, wherein the single-side thickness of the LATP layer is 10 microns, and the thickness of the aluminum foil is 12 microns.

[0079] The method for preparing the composite positive electrode sheet comprises the following steps:

[0080] S0, preparing the positive electrode body: exactly the same as step S1 of Example 1;

[0081] S1. Prepare a solid electrolyte solution: mix a solid electrolyte and a binder in a mass ratio of 7:3, wherein the solid electrolyte is selected from solid electrolyte LATP and the binder is selected from PVDF, and then add the mixture into NMP solvent and stir evenly to form a solid electrolyte solution, wherein the mass of the NMP solvent accounts for 80% of the mass of the solid electrolyte solution;

[0082] S2. The prepared solid electrolyte solution is evenly coated on the surface of the positive electrode body at a coating speed of 5 m / min and a coating pressure of 0.5 MPa. After coating, the positive electrode body is dried at 80° C. for 30 min to form a solid electrolyte layer and obtain a composite positive electrode sheet.

[0083] The composite positive electrode sheet prepared in this embodiment is assembled into a lithium-ion battery according to a conventional lithium battery manufacturing process, and a lithium-ion battery with high safety performance can be obtained.

[0084] Example 3

[0085] This embodiment provides a composite positive electrode plate, the composite positive electrode plate comprising: an aluminum foil, the aluminum foil having two opposite surfaces; a nickel cobalt manganese oxide layer, the nickel cobalt manganese oxide layer being arranged on two opposite surfaces of the aluminum foil; LLZO (Li7La3Zr2O 12 ) layer, the LLZO layer is arranged on the nickel cobalt manganese oxide layer, that is, the composite positive electrode plate consists of: LLZO layer + nickel cobalt manganese oxide layer + aluminum foil + nickel cobalt manganese oxide layer + LLZO layer, wherein the single-side thickness of the LLZO layer is 10 microns, and the thickness of the aluminum foil is 12 microns.

[0086] The method for preparing the composite positive electrode sheet comprises the following steps:

[0087] S0, preparing the positive electrode body: exactly the same as step S1 of Example 1;

[0088] S1. Prepare a solid electrolyte solution: mix a solid electrolyte and a binder in a mass ratio of 9:1, wherein the solid electrolyte is LLZO and the binder is PEO, and then add the mixture into an acetonitrile solvent and stir evenly to form a solid electrolyte solution, wherein the mass of the acetonitrile solvent accounts for 80% of the mass of the solid electrolyte solution;

[0089] S2. The prepared solid electrolyte solution is evenly coated on the surface of the positive electrode body at a coating speed of 5 m / min and a coating pressure of 0.5 MPa. After coating, the positive electrode body is dried at 80° C. for 30 min to form a solid electrolyte layer to obtain a composite positive electrode sheet.

[0090] The composite positive electrode sheet prepared in this embodiment is assembled into a lithium-ion battery according to a conventional lithium battery manufacturing process, and a lithium-ion battery with high safety performance can be obtained.

[0091] Example 4

[0092] The present embodiment provides a composite positive electrode plate, which includes: an aluminum foil having two opposite surfaces; a nickel cobalt lithium manganese oxide layer, which is arranged on two opposite surfaces of the aluminum foil; and a LATP layer, which is arranged on the nickel cobalt lithium manganese oxide layer. That is, the composite positive electrode plate is composed of: LATP layer + nickel cobalt lithium manganese oxide layer + aluminum foil + nickel cobalt lithium manganese oxide layer + LATP layer, wherein the single-side thickness of the LATP layer is 10 microns, and the thickness of the aluminum foil is 12 microns.

[0093] The method for preparing the composite positive electrode sheet comprises the following steps:

[0094] S0, the same as step S0 in Example 1;

[0095] S1. Prepare solid electrolyte solution: mix solid electrolyte and binder in a mass ratio of 9:1, wherein the solid electrolyte is solid electrolyte LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), PVDF is selected as the binder, and then the mixture is added to the NMP solvent and stirred evenly to form a solid electrolyte solution, wherein the mass of the NMP solvent accounts for 70% of the mass of the solid electrolyte solution;

[0096] S2. The prepared solid electrolyte solution is evenly coated on the surface of the positive electrode body at a coating speed of 7 m / min and a coating pressure of 5 MPa. After coating, the positive electrode body is dried at 100° C. for 20 min to form a solid electrolyte layer to obtain a composite positive electrode sheet.

[0097] The composite positive electrode sheet prepared in this embodiment is assembled into a lithium-ion battery according to a conventional lithium battery manufacturing process, and a lithium-ion battery with high safety performance can be obtained.

[0098] Comparative Example 1

[0099] The positive electrode sheet provided in this comparative example is the positive electrode body prepared in step S0 of Example 1.

[0100] Comparative Example 2

[0101] This comparative example provides a composite positive electrode plate, which includes: an aluminum foil having two opposite surfaces; a nickel cobalt manganese oxide and LATP composite layer, wherein the nickel cobalt manganese oxide and LATP composite layer is arranged on two opposite surfaces of the aluminum foil, that is, the composite positive electrode plate is composed of: nickel cobalt manganese oxide and LATP composite layer + aluminum foil + nickel cobalt manganese oxide and LATP composite layer, wherein the single-side thickness of the nickel cobalt manganese oxide and LATP composite layer is the same as the sum of the single-side thicknesses of the nickel cobalt manganese oxide layer and the LATP layer in Example 1, and the thickness of the aluminum foil is 12 microns.

[0102] The method for preparing the composite positive electrode sheet comprises the following steps:

[0103] Weigh NCM, SP, PVDF and solid electrolyte LATP. The mass of each raw material is the same as that in Example 1. Dissolve each raw material in NMP solvent to prepare a slurry. Apply the slurry on aluminum foil at a coating speed of 5 m / min and a coating pressure of 0.5 MPa. After coating, dry at 80°C for 60 min, and then roll-press (the rolling operation is the same as that in Example 1). After rolling, die-cut to obtain a composite positive electrode sheet with a length and width of 90×59 mm.

[0104] Performance Testing

[0105] The positive electrode sheets provided in the embodiments and comparative examples were tested for safety performance and electrochemical performance.

[0106] The positive electrode sheets provided in the embodiment and the comparative example are assembled into lithium-ion batteries according to a conventional lithium-ion battery manufacturing process. The conventional lithium-ion battery manufacturing process includes the following steps:

[0107] Positive electrode sheet: the composite positive electrode sheet provided in Examples 1-4 and Comparative Example 2 or the positive electrode sheet provided in Comparative Example 1;

[0108] Negative electrode sheet: The negative electrode slurry includes graphite, conductive agent (SP), binder (SBR) and thickener (CMC) in a mass ratio of 95.5:1:2:1.5; the negative electrode slurry is coated on the copper foil, and the single-sided surface density of the coating is 11.5mg / cm 2, after rolling and die cutting, a negative electrode sheet with a length and width of 93×62 mm was obtained;

[0109] Diaphragm: The diaphragm is PP diaphragm;

[0110] The positive electrode sheet / diaphragm / negative electrode sheet are stacked, and after stacking, they are packaged in a soft package, injected with liquid, and sealed to obtain a 5Ah battery.

[0111] The test method of battery puncture test: Use a 5mm diameter steel needle to pierce the battery at a speed of 25mm / s, stay inside the battery for 60 minutes, and observe whether there is fire or explosion. If there is no fire or explosion, the test has passed.

[0112] The test method of battery overcharge test: the initial voltage of the battery is 4.2V, and it is charged with a constant current of 1C until it reaches 6.3V or the charging time reaches 1h. Stop charging and observe whether there is fire or explosion. If there is no fire or explosion, the test has passed.

[0113] Battery short circuit test method: Place the battery in a thermostat and set the temperature to 20℃±5℃. The initial voltage of the battery is 4.2V. The positive and negative electrodes of the battery are short-circuited externally for 10 minutes. The external circuit resistance should be less than 5mΩ. Observe for 1 hour to see if there is any fire or explosion. If there is no fire or explosion, the test is passed.

[0114] The test method for battery cycle performance is as follows: ① Discharge at a constant current of 1C to the termination voltage (2.5V) and stop discharging, and let it stand for 30 minutes; ② Charge at a constant current of 1C to the termination voltage (4.2V), switch to constant voltage charging, and stop charging until the charging current drops to 0.05C, and let it stand for 30 minutes; ③ Discharge at a constant current of 1C to the termination voltage and stop discharging, let it stand for 30 minutes, and record the discharge capacity; ④ Cycle continuously for 500 times according to ②~③, and take the ratio of the 500 discharge capacity to the first discharge capacity as the discharge capacity retention rate.

[0115] The test results are shown in Table 1.

[0116] Table 1

[0117]

[0118] From Table 1, we can see at least the following points:

[0119] (1) By comparing Examples 1-4 with Comparative Example 1, it can be seen that the discharge capacity retention rate of the battery containing the coated solid electrolyte layer after 500 cycles is basically the same as that of Comparative Example 1, and the cycle performance is excellent. At the same time, the results of the acupuncture, overcharge and short-circuit tests show that the positive electrode plate coated with the solid electrolyte layer exhibits good safety performance when applied to lithium-ion batteries. By providing a solid electrolyte layer on the positive electrode active material layer, the present invention can help the battery pass the acupuncture, overcharge and short-circuit tests while balancing the electrical performance of the battery, thereby comprehensively improving the safety of lithium-ion batteries.

[0120] (2) By comparing Example 1 with Example 2, it can be seen that the increase in the proportion of the binder has an inhibitory effect on the transmission and migration of lithium ions, which will reduce the ionic conductivity and the cycle performance of the battery will be lost.

[0121] (3) By comparing Example 1 with Comparative Example 2, it can be seen that doping the solid electrolyte into the positive electrode active material cannot make the battery pass the needle penetration test, and the cycle performance is significantly reduced.

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite positive electrode sheet, characterized in that: The composite positive electrode sheet comprises: A positive electrode current collector (1), wherein the positive electrode current collector (1) has two opposite surfaces; A positive electrode active material layer (2), the positive electrode active material layer (2) being arranged on at least one surface of the positive electrode current collector (1); A solid electrolyte layer (3), wherein the solid electrolyte layer (3) is arranged on the positive electrode active material layer (2).

2. The composite positive electrode sheet according to claim 1, characterized in that: The positive electrode current collector (1) comprises aluminum foil; And / or, the positive electrode active material layer (2) comprises a positive electrode active material, and the positive electrode active material comprises one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate, and lithium manganese oxide; and / or, the thickness of the solid electrolyte layer (3) is 5 to 15 micrometers; And / or, the solid electrolyte layer (3) comprises a solid electrolyte, and the solid electrolyte comprises at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, LLTO, and LLZTO; And / or, the solid electrolyte layer (3) further comprises a binder, wherein the binder comprises at least one of PVDF and PEO.

3. The composite positive electrode sheet according to claim 2, characterized in that: The mass ratio of the solid electrolyte to the binder is (70-95):(5-30).

4. A method for preparing a composite positive electrode sheet according to any one of claims 1 to 3, characterized in that: The preparation method comprises: S1, mixing a solid electrolyte and a binder to obtain a mixture, then adding the mixture to a solvent and stirring evenly to obtain the solid electrolyte solution; S2. Applying the solid electrolyte solution on the positive electrode body and drying it to obtain the composite positive electrode sheet, wherein the positive electrode body comprises the positive electrode collector (1) and the positive electrode active material layer (2) arranged on at least one surface of the positive electrode collector (1).

5. The method for preparing a composite positive electrode sheet according to claim 4, characterized in that: The solid electrolyte includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, LLTO, and LLZTO; the binder includes at least one of PVDF and PEO; and the solvent includes at least one of NMP and acetonitrile; And / or, the mass ratio of the solid electrolyte to the binder is (70-95):(5-30); And / or, in step S1, the mass of the solvent in the solid electrolyte solution accounts for 65% to 85% of the mass of the solid electrolyte solution.

6. The method for preparing a composite positive electrode sheet according to claim 4, characterized in that: In step S2, during the coating process, the coating speed is 1-10 m / min; and / or, in step S2, during the coating process, the coating pressure is 0.1 to 10 MPa; And / or, in step S2, the drying temperature is 80-120° C., and the drying time is 5-30 min.

7. The method for preparing a composite positive electrode sheet according to claim 4, characterized in that: The preparation method of the positive electrode body comprises: preparing the positive electrode active material, the conductive agent and the binder into a positive electrode slurry, coating the positive electrode slurry on the positive electrode current collector (1) to obtain the positive electrode active material layer (2), and then rolling and die-cutting to obtain the positive electrode body.

8. The method for preparing a composite positive electrode sheet according to claim 7, characterized in that: In the preparation process of the positive electrode body, the conductive agent includes at least one of conductive carbon black, Ketjen black, acetylene black, carbon nanotubes, and graphene, and the binder includes at least one of PVDF, polytetrafluoroethylene, polyacrylonitrile, polyvinyl alcohol, and polyacrylic acid.

9. The method for preparing a composite positive electrode sheet according to claim 7, characterized in that: During the preparation of the positive electrode body, the single-sided surface density of the coating is 15-25 mg / cm 2 .

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite positive electrode sheet according to any one of claims 1 to 3 or the composite positive electrode sheet prepared by the preparation method according to any one of claims 4 to 9.

Citation Information

Patent Citations

  • Lithium ion battery electrode sheet with a solid electrolyte layer and a coating method thereof

    CN109273760A

  • Composite electrode, preparation method thereof and application of composite electrode in solid-state lithium ion battery

    CN111403750A

  • Composite positive plate as well as preparation method and application thereof

    CN116741942A

  • Inorganic solid electrolyte composite slurry, method for preparing, application and lithium-ion battery having the same

    US20190027780A1

  • Positive Electrode for Lithium Secondary Battery, Method for Manufacturing the Same, and Lithium Secondary Battery Including the Same

    US20220293930A1

Cited By

  • Composite pole piece and preparation method thereof

    CN120581535A

  • Method for manufacturing electrode member, electrode, and lithium secondary battery

    CN121528870A